A QUAD-REGENCY STUDY: FINANCIAL LITERACY, SOCIAL ENVIRONMENT, AND ADOLESCENT FINANCIAL BEHAVIOR IN WEST JAVA, INDONESIA - Joharudin, Agus; Muhibudin Wijaya Laksana (Media Ekonomi, 2024)
This study examines the influence of financial literacy and social environment as independent drivers of financial behavior among high school students in West Java, Indonesia. It further investigates regional variations across four socioeconomically distinct regencies/cities (Cirebon, Bogor, Bandung Barat, Tasikmalaya) to identify context-specific behavioral pathways. A quantitative cross-sectional design was employed, collecting data from 200 students (50 per regency) via a 5-point Likert scale questionnaire. Variables included financial literacy (8 items), social environment (6 items), and financial behavior (8 items), adapted from OECD/INFE and prior literature. Purposive stratified sampling ensured regional representation. Data analysis used multiple linear regression and diagnostic tests. This study reveals that financial knowledge is the primary force shaping money management habits among West Java's high school students, while surprisingly, social influences from family and peers play minimal roles in their overall financial decisions. However, location dramatically reshapes this pattern: in industrial communities like Bandung Barat, classroom learning most strongly guides financial actions, whereas in agricultural areas like Tasikmalaya, local traditions and family practices carry meaningful weight. These insights highlight that effective financial education must adapt to regional economic landscapes.